Analisis Bottom Ash Limbah Batu Bara PLTU Pulang Pisau Sebagai Agregat Halus Pada Campuran Beton: Analysis Of Bottom Ash From Pulang Pisau Coal Plant Waste As Fine Aggregate For Concrete Mixture - Diharyo Diharyo; Norseta Ajie Saputra; Ignatius Delon; Naswa Nabila; Priska Priska; Sabila Ika Cahyani; Meliyana Anita; Octafiana Indah Rohani; Prenki Prenki (Media Ilmiah Teknik Sipil, 2026)
Bottom ash is a solid waste product of coal combustion at coal-fired power plants (PLTU), the volume of which continues to increase in line with growing energy demand. One potential use of bottom ash is as a substitute for fine aggregate in concrete mixes, thereby reducing the use of natural sand and minimizing the environmental impact of waste disposal. This study aimed to analyze the physical characteristics of bottom ash from the Pulang Pisau PLTU and evaluate its compliance with SNI 1969-2008 and SNI 1970-2008 testing requirements. The research phases included bottom ash sampling, physical characteristic testing (gradation analysis, specific gravity, water absorption value, and silt content), and subsequent evaluation against standard characteristics in accordance with SNI 1969-2008 and SNI 1970-2008. The results showed that the bottom ash from the Pulang Pisau PLTU had a fine, irregular gradation, a specific gravity lower than natural sand, and high porosity, potentially affecting the water absorption rate of the concrete. Overall, the bottom ash from the Pulang Pisau PLTU (Coal-fired Power Plant) is deemed suitable for use as an alternative to fine aggregate in concrete mixes. This utilization not only supports the reduction of natural aggregate use but also provides a more sustainable solution for industrial waste management.